2021
DOI: 10.1111/jre.12933
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA Lrp6 promotes cementoblast differentiation via miR‐145a‐5p/Zeb2 axis

Abstract: Background and Objective: Cementum is a part of the periodontium and anchors periodontal ligaments to the alveolar bone. Cementoblasts are responsible for the cementum formation via matrix deposition and subsequently mineralization. Thus, exploring novel mechanisms underlying the function of cementoblast contributes to the treatment of cementum damage. Recently, circRNA Lrp6 (circLRP6) has been of interest due to its active role in cell differentiation, but its potential role in cementoblast differentiation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…However, the majority of lncRNAs have not been investigated for roles in cementoblast mineralization in vitro and in vitro. Although previous research has demonstrated that CircRNA Lrp6 promotes cementoblast mineralization, 43 circular RNA expression profile was not determined by RNA sequencing during cementoblast mineralization. Meanwhile, the roles of lncRNAs in epigenetics are still unexplored during cementoblast mineralization.…”
Section: Discussionmentioning
confidence: 96%
“…However, the majority of lncRNAs have not been investigated for roles in cementoblast mineralization in vitro and in vitro. Although previous research has demonstrated that CircRNA Lrp6 promotes cementoblast mineralization, 43 circular RNA expression profile was not determined by RNA sequencing during cementoblast mineralization. Meanwhile, the roles of lncRNAs in epigenetics are still unexplored during cementoblast mineralization.…”
Section: Discussionmentioning
confidence: 96%
“…The circLRP6 2-2 -probe-captured FGF9 mRNAs were analyzed by qPCR. **P < 0.01. involved in cell cycle, proliferation, and apoptosis of cells including tumor cells and smooth muscle cells [17][18][19][20][21][22], they might not show the same effect in cardiomyocytes. Moreover, according to the RNA-seq data of Werfel et al [8], only circRNA formed by the second exon of LRP6 gene was robustly detected in heart samples of species across human, mouse, and rat, implying its evolutionary indispensability in animal hearts.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of these circRNAs will result in heart diseases [5,15,16]. Although other distinct circular transcripts of LRP6 were reported to be involved in cell cycle, proliferation, and apoptosis of cells including tumor cells and smooth muscle cells [17–22], they might not show the same effect in cardiomyocytes. Moreover, according to the RNA‐seq data of Werfel et al .…”
Section: Discussionmentioning
confidence: 99%
“…For osteoblast, circ_0008500 remained upregulated during osteoblast differentiation and promoted osteoblast mineralization via sponging miR‐1301‐3p 52 . One recent study showed that circLrp6 promoted cementoblast differentiation by regulating Zeb2 53 …”
Section: Discussionmentioning
confidence: 99%